The approach for competences from the persepective of the human development: basic aspects and curricular design - Martínez Carpio, Héctor E. (2013)
The article proposes a view of the competence approach from the perspective of human development. It begins with theoretical aspects of human development, where it criticizes the economistic model of GDP and emphasizes the quality model of life proposed by UNDP. As a result, within the challenges of the new century university proposes a concept of competence where it is important to underscore the development of skills and values for the development of a life plan. Looking deeply into explains the meaning of, social construction, significant learning, the need to implement competition through skills and values, metacognition and life project. Similarly, there is finally one student graduate profile and curriculum planning proposal, based on a “course training program” which allows operationalize the skills and values as well as the methodology, and skills assessment.